2008
DOI: 10.1115/1.2993543
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study of Solidification in a Spherical Shell

Abstract: The present study explores numerically and experimentally the process of a phase-change material (PCM) solidification in a spherical shell. At the initial state, the PCM liquid occupies 98.5% of the shell. The upper segment of 1.5% contains air, which flows in as the solidification progresses. In the experiments, a commercially available paraffin wax is used. Its properties are engaged in the numerical simulations. The investigation is performed for solidification in spherical shells of 20 mm, 40 mm, 60 mm, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(50 citation statements)
references
References 20 publications
4
44
0
Order By: Relevance
“…This optimum frequency was used for all other experiments in the study. The solidification time result of 30 minutes without vibration shown in Table 2 compares well with the numerical and experimental results presented by Assis et al [9], where the solidification time shown for 40 mm paraffin wax samples without vibration was approximately 36 minutes. The difference of 6 minutes may be due to the paraffin wax that was used by Assis et al [9], having had a lower solidfication temperature than the one used in this study by a difference of about 7°C.…”
Section: Solidification Timessupporting
confidence: 78%
See 1 more Smart Citation
“…This optimum frequency was used for all other experiments in the study. The solidification time result of 30 minutes without vibration shown in Table 2 compares well with the numerical and experimental results presented by Assis et al [9], where the solidification time shown for 40 mm paraffin wax samples without vibration was approximately 36 minutes. The difference of 6 minutes may be due to the paraffin wax that was used by Assis et al [9], having had a lower solidfication temperature than the one used in this study by a difference of about 7°C.…”
Section: Solidification Timessupporting
confidence: 78%
“…Experiments were conducted with spherical geometries because a comparison (although limited) could be made to work presented by Assis et al [9], which studied the numerical and experimental solidification of paraffin wax, however, without vibration. One of the diameters studied was the same as in this study and therefore used for verification purposes.…”
Section: Experimental Methods and Proceduresmentioning
confidence: 99%
“…They provided a correlation for the melting fraction versus an appropriate combination of the Grashof, Stefan and Fourier numbers. Also, they performed another combined experimental and numerical study on the solidification of PCM inside a spherical shell with various diameters [7]. Tan et al [8] conducted experimental and computational study on melting of PCM inside a spherical capsule.…”
Section: Introduction and Literature Reviewmentioning
confidence: 98%
“…The paraffin filled about 85% of the volume, while the remaining region was filled with air, modeled as compressible ideal gas, whose properties can also be found in Table 1. The thermal physical parameters used in this paper were taken from the reference [23]. RT27 had a liquidus temperature of 303 K and a solidus temperature of 301 K. Other relevant properties of the material were treated as constants in the fully solid or liquid state, but not as constants in the mushy zone, where they varied linearly with temperature, until they reached the constant value in the liquid and solid zones, as listed in Table 1.…”
Section: Physical and Numerical Modelmentioning
confidence: 99%